Rainfall network optimization in Johor - Mohd. Aziz, Mohd. Khairul Bazli (2014)
This paper presents a method for establishing an optimal network design of rain gauge station for the estimation of areal rainfall in Johor. The main problem in this study is minimizing an objective function to determine the optimal number and location for the rain gauge stations. The well-known geostatistics method (variance-reduction method) is used in combination with simulated annealing as an algorithm of optimization. Rainfall data during monsoon season (November – February) for 1975 – 2008 from existing 84 rain gauge stations covering all Johor were used in this study. Result shows that the combination of geostatistics method with simulated annealing successfully managed to determine the optimal number and location of rain gauge station.